Nanoelectronics devices, circuits and systems - Kaushik, Brajesh Kumar (Micro & nano technologies, 2019)
Nanoelectronics: Devices, Circuits and Systems explores current and emerging trends in the field of nanoelectronics, from both a devices-to-circuits and circuits-to-systems perspective. It covers a wide spectrum and detailed discussion on the field of nanoelectronic devices, circuits and systems. This book presents an in-depth analysis and description of electron transport phenomenon at nanoscale dimensions. Both qualitative and analytical approaches are taken to explore the devices, circuit functionalities and their system applications at deep submicron and nanoscale levels. Recent devices, including FinFET, Tunnel FET, and emerging materials, including graphene, and its applications are discussed. In addition, a chapter on advanced VLSI interconnects gives clear insight to the importance of these nano-transmission lines in determining the overall IC performance. The importance of integration of optics with electronics is elucidated in the optoelectronics and photonic integrated circuit sections of this book. This book provides valuable resource materials for scientists and electrical engineers who want to learn more about nanoscale electronic materials and how they are used.Shows how electronic transport works at the nanoscale levelDemonstrates how nanotechnology can help engineers create more effective circuits and systemsAssesses the most commonly used nanoelectronic devices, explaining which is best for different situations